Weak topological insulators induced by the interlayer coupling: A first-principles study of stacked Bi 2 TeI - Tang, Peizhe; Yan, Binghai; Cao, Wendong; Wu, Shu-Chun; Felser, Claudia; Duan, Wenhui (Physical Review B - Condensed Matter and Materials Physics, 2014)
Based on first-principles calculations, we predict Bi2TeI, a stoichiometric compound that is synthesized, to be a weak topological insulator (TI) in layered subvalent bismuth telluroiodides. Within a bulk energy gap of 80 meV, two Dirac-cone-like topological surface states exist on the side surface perpendicular to the BiTeI layer plane. These Dirac cones are relatively isotropic due to the strong interlayer coupling, distinguished from those of previously reported weak TI candidates. Moreover, with chemically stable cladding layers, the BiTeI-Bi2-BiTeI sandwiched structure is a robust quantum spin Hall system, which can be obtained by simply cleaving the bulk Bi2TeI. © 2014 American Physical Society.
CRIS-Team Scopus Importer:2023-03-20